Randomized Sham-Controlled Pilot Study of Neurocardiac Function in Patients With Acute Ischaemic Stroke Undergoing Heart Rate Variability Biofeedback - Siepmann, Timo; Ohle, Paulin; Sedghi, Annahita; Simon, Erik; Arndt, Martin; Pallesen, Lars-Peder; Ritschel, Gerhard; Barlinn, Jessica; Reichmann, Heinz; Puetz, Volker; Barlinn, Kristian (Frontiers in Neurology, 2021)
Background: Neurocardiac dysfunction worsens clinical outcome and increases mortality in stroke survivors. We hypothesized that heart rate variability (HRV) biofeedback improves neurocardiac function by modulating autonomic nervous system activity after acute ischaemic stroke (AIS). Methods: We randomly allocated (1:1) 48 acute ischaemic stroke patients to receive nine sessions of HRV- or sham biofeedback over three days in addition to comprehensive stroke unit care. Before and after the intervention patients were evaluated for HRV via standard deviation of normal-to-normal intervals (SDNN, primary outcome), root mean square of successive differences between normal heartbeats (RMSSD), a predominantly parasympathetic measure, and for sympathetic vasomotor and sudomotor function. Severity of autonomic symptoms was assessed via survey of autonomic symptom scale total impact score (TIS) at baseline and after three months. Results: We included 48 patients with acute ischaemic stroke (19 females, ages 65 [4.4], median [interquartile range]). Treatment with HRV biofeedback increased HRV post intervention (SDNN: 43.5 [79.0] ms vs. 34.1 [45.0] ms baseline, p=0.015; RMSSD: 46.0 [140.6] ms vs. 29.1 [52.2] ms baseline, p=0.015) and alleviated autonomic symptoms after three months (TIS 3.5 [8.0] vs. 7.5 [7.0] baseline, p=0.029), which was not seen after sham biofeedback (SDNN: p=0.63, RMSSD: p=0.65, TIS: 0.06). There were no changes in sympathetic vasomotor and sudomotor function (p=ns). Conclusions: Adding HRV biofeedback to standard stroke unit care led to improved neurocardiac function and sustained alleviation of autonomic symptoms after acute ischaemic stroke, which was likely mediated by a predominantly parasympathetic mechanism. Clinicaltrials.gov identifier: NCT03865225